The Implementation of Curriculum 2013 in English Subject at SMA Negeri in Ternate - S Syamsia; Suhaimi Tegamuni (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2018)
This research focused on the implementation of curriculum 2013 in English subject at SMA Negeri in Ternate. In Ternate, curriculum 2013 has implemented. Such as some senior high school that the researcher took as samples in this research. This research used qualitative approach with descriptive method. The population of this research are 12 SMA in Ternate. And the samples of this research are 3 (three) of 12 SMA in Ternate. The data collection used in this research are: observation, quetionaire, and documentation. To analyze the data, the researcher used reduction data, presentation data, and verification data. The implementation of K 13 in English subject in school A and C Ternate can be neglected because the K 13 is not implemented. The implementation of K 13 in English subject in school B Ternate is implemented. The learning process of English based on lesson plan. From 9 items of main activities based on lesson plan there were 8 activities implemented and only one activity didn’t implemented it was basic competence and indicator. Hereby the researchers take conclusion that the implementation of K13 in English subject in school B is good.